Penerapan Aromaterapi Lemon terhadap Penurunan Nyeri pada Pasien Post Operasi Fibrosarcoma: (Studi Kasus Keperawatan) - Shidqi Auliaa Yudha; Tri Sumarni (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Introduction: Fibrosarcoma is a rare soft tissue malignancy that may require surgical treatment. Postoperative patients are at risk of acute pain, impaired skin/tissue integrity, and nutritional deficit, which may delay recovery. Structured nursing care is needed to reduce symptoms, prevent wound complications, and improve nutritional tolerance. Method: This article used a descriptive design with a case study approach. The subject was a 40-year-old male patient with a postoperative medical diagnosis of fibrosarcoma. Data were collected through nursing assessment, observation, physical examination, review of supporting examination results, therapy records, nursing implementation, and nursing evaluation over 3 × 24 hours. Results: The assessment identified three main nursing diagnoses: acute pain related to physical injury agents, impaired skin/tissue integrity related to mechanical factors from surgical procedures, and nutritional deficit related to impaired nutrient absorption. Nursing interventions included pain management using lemon aromatherapy and analgesic collaboration, sterile wound care, infection sign monitoring, nutritional management, gastrointestinal function monitoring, and patient-family education. After 3 × 24 hours of care, the pain scale decreased from 6 to 2, the wound appeared dry with well-approximated edges and no pus, redness, edema, or dehiscence, and the patient was able to eat without nausea with oral intake increasing to three-fourths of the meal portion. Conclusion: Structured nursing care in a postoperative fibrosarcoma patient helped reduce pain, improve wound condition, and increase nutritional tolerance. Lemon aromatherapy may be used as a non-pharmacological adjunct to analgesics in suitable patients.